Risk Management in Private Companies and Public Sector Organizations: A Preliminary Comparative Study - Dominicus Priyarsono; Raden Racmadi Gustrian; Charles R. Vorst; Heri Supriyadi; A. Yulian; Y. Munawar (Jurnal Organisasi dan Manajemen, 2023)
Purpose – The effectiveness of risk management in an organization depends largely on its organizational culture as revealed in its governance structure and organizational process. The research question of this study is how to develop strategy to improve the effectiveness of risk management under the constraints of a given organizational culture. The objective of this study is to show that there are fundamental differences and similarities between the governance structure and organizational process that significantly influence the effectiveness of risk management in private companies and the one in public sector organizations. Methodology – To achieve the objective, legal documents of major public and private organizations are reviewed and key resource persons working for the organizations are interviewed. Findings – This paper reports preliminary results that identify several important dimensions of governance structure and organizational process in both sectors that crucially influence the effectiveness of risk management.  Originality – Studies on the similarities and differences between public and private organizations in implementing risk management have been very rare. Very few studies explicitly address the effectiveness of risk management in the perspective of the comparative study.  This study has never been carried out before, at least in the Indonesian context.